2020
DOI: 10.20870/oeno-one.2020.54.4.3756
|View full text |Cite
|
Sign up to set email alerts
|

A vine physiology-based terroir study in the AOC-Lavaux region in Switzerland

Abstract: Understanding how different pedoclimatic conditions interact with vine and berry physiology, and subsequently impact wine quality, is paramount for an good valorization of viticultural terroirs and can help to optimize mitigation strategies in the face of global warming.The aim of the present study was to establish terroir zones in a steep slope region in Switzerland based on vine and berry physiology. The study area, Villette in the AOC Lavaux, was a unique experimental site due to the homogeneity of plant ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
(69 reference statements)
3
7
1
Order By: Relevance
“…On the other hand, in the present study, phenological timing was found to be clearly driven by the elevation gradient when each vegetative season was considered separately. Our findings are in accordance with those reported by Rienth et al (2020). In our study, a relevant vintage effect that influenced both vine and berry physiology was observed; however, elevation was found to be the leading driver of precocity in all the years of the study (2017)(2018)(2019).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, in the present study, phenological timing was found to be clearly driven by the elevation gradient when each vegetative season was considered separately. Our findings are in accordance with those reported by Rienth et al (2020). In our study, a relevant vintage effect that influenced both vine and berry physiology was observed; however, elevation was found to be the leading driver of precocity in all the years of the study (2017)(2018)(2019).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, in the present study, the vineyard average temperatures recorded during the grape vegetative period varied depending on site elevation within a range of 0 to 2 °C, and they significantly affected the phenological timing of Pinot blanc. This result corresponds to the findings of previous studies by Failla et al (2004) on the Nebbiolo grape in the Alpine environment, and by Valtellina and Rienth et al (2020) on Chasselas in the AOC-Lavaux region in Switzerland, in which the vertical temperature gradient, due to elevation, was found to have a direct influence on bud break, flowering and technological maturity dates. Indeed, air temperature is considered one of the most important factors which drive the growth and development of grapevines (Winkler, 1974;Fraga et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A changing climate requires a profound knowledge of how abiotic factors modulate different quality-determining compounds of the grape berry in order to implement appropriate viticultural mitigation strategies (van Leeuwen and Destrac-Irvine, 2017;Rienth et al, 2020), select varieties, clones (Wolkovich et al, 2018), and rootstocks (Ollat et al, 2016), and to identify traits, genes, or QTLs for the breeding of new cultivars better adapted to future conditions (Duchêne, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The observed climate changes, such as an increase in the average ambient temperature, an increase in the shortage of fresh water, make adjustments to the metabolism of the grape, which affects the quality of berries and wine products, up to the transformation of the style of wines [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%